2011
DOI: 10.1093/jnci/djr495
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Partial Breast Irradiation Using Brachytherapy for Breast Cancer: Patterns in Utilization and Guideline Concordance

Abstract: APBIb after breast-conserving surgery has been rapidly adopted in the United States. Use varied by race, ethnicity, and widely by region, especially among patients who may not be suitable for this radiation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 48 publications
5
37
0
Order By: Relevance
“…[10][11][12][13] Our study furthers the discussion and evaluates the effect of increasing PBI rates on overall RT use. There was a noticeable increase in the use of PBI after 2004, which coincides with the approval of Medicare reimbursement for balloon brachytherapy.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[10][11][12][13] Our study furthers the discussion and evaluates the effect of increasing PBI rates on overall RT use. There was a noticeable increase in the use of PBI after 2004, which coincides with the approval of Medicare reimbursement for balloon brachytherapy.…”
Section: Discussionmentioning
confidence: 80%
“…A course of PBI can be completed within 5 days, and many have speculated that the availability of such a modality would increase the use of RT. Indeed, there has been a dramatic uptake in the use of PBI since its introduction in the early 2000s, [10][11][12][13] but few studies have explored the coincident effect on overall rates of RT, particularly among populations who might benefit most from the availability of a shorter treatment schedule.…”
mentioning
confidence: 99%
“…To our knowledge, no study has yet documented the trends in utilization of BCT vs mastectomy since APBI has become more broadly used, and we would welcome research toward this end. The population-based studies that have been published have found that brachytherapy-based APBI has been most prevalent in renowned tertiary care hospitals and advanced cancer centers [85].This difference in treatment delivery may be due to both patient preference and available resources, as HDR brachytherapy and the expert team are not available in centers in rural areas. So far, there has been no published documentation on the trends in usage of external beam -based APBI in these center.…”
Section: Comparison Of Apbi Modalities:-mentioning
confidence: 99%
“…This concept has been challenged by approaches focussing on more convenient treatment providing a lower total radiation dose given in fewer slightly larger fractions and delivered over a shorter period of time by use of hypofractionation schedules [35,36,37]. In addition, the necessity of applying WBI in all patients was questioned by the idea of partial breast irradiation (PBI) [38,39,40,41]. The combination of these techniques, accelerated partial breast irradiation (APBI), was also subject of recently published studies [42].…”
Section: Adjuvant Radiotherapymentioning
confidence: 99%